Design and development of combat robot for military applications - Raju Hajare; Mallikarjuna Gowda C.P (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
In this paper we have developed a combat robot which will assist our commandos to fight against terrorism. With additional weaponry system it can perform other tasks also. Our preliminary aim in this project is to design a combat robot which can be used to handle the unmanned situations like terror attack inside the building where the firing is heavy and the entry of commandos may be difficult. In such situations the combat robot with spy camera, which is controlled through the control room can be sent into the terrorist occupied area. The robot constantly sends the visuals captured through spy camera to the control room. Based on the visuals received from the robot the control room operator can give directions to the robot. This kind of spy robot can also be used in star hotels, shopping malls, jewelry show rooms.